Intellectual Capital Analysis of Employee Performance in the Culinary Industry PT Sinergitas Indonesia Muda (Suweger Indonesia) - Maulidiyah Kartikasari; Gendut Sukarno (PT FORMOSA CENDEKIA GLOBAL, 2023)
The main objective of this research is to investigate the impact of intellectual capital on the job performance of employees working in the culinary sector that is PT. Sinergitas Indonesia Muda (Suweger Indonesia). The method employed for selecting participants in this study was purposive sampling, whereby individuals were specifically chosen based on predetermined criteria. so that the number of samples taken was 60 employees. The analysis technique used in this study is smart partial least squares (PLS). The analysis findings indicate that (1) there is a noteworthy and favorable impact of human capital on the performance of employees at PT. Sinegrtias Indonesia Muda (Suweger Indonesia) (2) there is no significant adverse impact of structural capital on the performance of employees at PT. Sinergitas Indonesia Muda (Suweger Indonesia) (3) relational capital has a beneficial impact on the performance of employees at PT. Sinergitas Indonesia Muda.